2015
DOI: 10.1371/journal.pone.0123826
|View full text |Cite
|
Sign up to set email alerts
|

Parity of Indigenous and Non-Indigenous Women in Brazil: Does the Reported Number of Children Born Depend upon Who Answers National Census Questions?

Abstract: Taking parity as the main analytic variable, the objective of this study is to investigate whether the patterns of response to national census questions in Brazil differ when Indigenous and non-Indigenous women are compared, taking into consideration whether the information was provided by the women directly or by a proxy respondent (another household member or a non-resident). We use data on children ever born to Indigenous and non-Indigenous women from two Brazilian regions, the Northeast and the North. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Previous studies have found that anemia is highly prevalent in Indigenous populations in Brazil, especially among children [ 9 , 10 ]. There is limited information available on the epidemiology of anemia among adult Indigenous women, despite the vulnerabilities of this group, which often include bearing a first child at an early age and high parity throughout their reproductive years [ 11 13 ]. Among the Xavante Indians from Central Brazil, 54.2 % of adult women from 20–40 years of age had anemia [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that anemia is highly prevalent in Indigenous populations in Brazil, especially among children [ 9 , 10 ]. There is limited information available on the epidemiology of anemia among adult Indigenous women, despite the vulnerabilities of this group, which often include bearing a first child at an early age and high parity throughout their reproductive years [ 11 13 ]. Among the Xavante Indians from Central Brazil, 54.2 % of adult women from 20–40 years of age had anemia [ 14 ].…”
Section: Introductionmentioning
confidence: 99%